Real-Time Rendering of Plant Leaves - Wang, Lifeng; Wang, Wenle; Dorsey, Julie; Yang, Xu; Guo, Baining; Shum, Heung-Yeung (Association for Computing Machinery, Inc., 2005)
This paper presents a framework for the real-time rendering of plant leaves with global illumination effects. Realistic rendering of leaves requires a sophisticated appearance model and accurate lighting computation. For leaf appearance we introduce a parametric model that describes leaves in terms of spatially-variant BRDFs and BTDFs. These BRDFs and BTDFs, incorporating analysis of subsurface scattering inside leaf tissues and rough surface scattering on leaf surfaces, can be measured from real leaves. More importantly, this description is compact and can be loaded into graphics hardware for fast run-time shading calculations, which are essential for achieving high frame rates. For lighting computation, we present an algorithm that extends the Precomputed Radiance Transfer (PRT) approach to all-frequency lighting for leaves. In particular, we handle the combined illumination effects due to lowfrequency environment light and high-frequency sunlight. This is done by decomposing the local incident radiance of sunlight into direct and indirect components. The direct component, which contains most of the high frequencies, is not pre-computed with spherical harmonics as in PRT; instead it is evaluated on-the-fly using pre-computed light-visibility convolution data. We demonstrate our framework by the rendering of a variety of leaves and assemblies thereof.